Whole-Body Biodistribution, Dosimetry, and Metabolite Correction of [C]Palmitate: A PET Tracer for Imaging of Fatty Acid Metabolism - Nana L. Christensen MLS; Steen Jakobsen PhD; Anna C. Schacht PhD; Ole L. Munk PhD; Aage K. O. Alstrup DVM, PhD; Lars P. Tolbod PhD; Hendrik J. Harms PhD; Søren Nielsen MD, PhD; Lars C. Gormsen MD, PhD (Molecular Imaging)
Introduction: Despite the decades long use of [ 11 C]palmitate positron emission tomography (PET)/computed tomography in basic metabolism studies, only personal communications regarding dosimetry and biodistribution data have been published. Methods: Dosimetry and biodistribution studies were performed in 2 pigs and 2 healthy volunteers by whole-body [ 11 C]palmitate PET scans. Metabolite studies were performed in 40 participants (healthy and with type 2 diabetes) under basal and hyperinsulinemic conditions. Metabolites were estimated using 2 approaches and subsequently compared: Indirect [ 11 C]CO 2 release and parent [ 11 C]palmitate measured by a solid-phase extraction (SPE) method. Finally, myocardial fatty acid uptake was calculated in a patient cohort using input functions derived from individual metabolite correction compared with population-based metabolite correction. Results: In humans, mean effective dose was 3.23 (0.02) µSv/MBq, with the liver and myocardium receiving the highest absorbed doses. Metabolite correction using only [ 11 C]CO 2 estimates underestimated the fraction of metabolites in studies lasting more than 20 minutes. Population-based metabolite correction showed excellent correlation with individual metabolite correction in the cardiac PET validation cohort. Conclusion: First, mean effective dose of [ 11 C]palmitate is 3.23 (0.02) µSv/MBq in humans allowing multiple scans using ∼300 MBq [ 11 C]palmitate, and secondly, population-based metabolite correction compares well with individual correction.